Anisodamine Suppressed the Growth of Hepatocellular Carcinoma Cells, Induced Apoptosis and Regulated the Levels of Inflammatory Factors by Inhibiting NLRP3 Inflammasome Activation - Li P; Liu Y; He Q (Dove Medical Press, 2020)
Ping Li, Yu Liu, Qiang He Department of Hepatobiliary Surgery, Beijing Chaoyang Hospital, Capital Medical University, Beijing 100020, People’s Republic of ChinaCorrespondence: Qiang HeDepartment of Hepatobiliary Surgery, Beijing Chaoyang Hospital, Capital Medical University, No. 8, Gongti South Road, Chaoyang District, Beijing 100020, People’s Republic of ChinaTel + 86-010-85231504Email heqiang349@sina.comIntroduction: Hepatocellular carcinoma (HCC) is a primary liver cancer with a 5-year incidence of over 70%. Anisodamine (ANI), an alkaloid extracted from Anisodus, has a good therapeutic effect in septic shock and morphine addiction. Our study designed to investigate the anticancer effect of anisodamine (ANI) on HCC.Materials and Methods: HepG2 cells were subcutaneously injected into BALB/C nude mice and the tumor tissue was subcutaneously inoculated to construct the transplanted tumor. Mice were randomly divided into 10 groups (n = 5): control group, ANI-10 group, ANI-50 group, ANI-200 group, ANI-200+pcDNA-NLRP3 group, ANI-200+EV group, sh-NLRP3 group, ANI-200 + sh-NLRP3 group, normal group and normal+ANI-200 group.Results: Studies indicated that ANI inhibited the growth of HCC xenografts and reduced liver damage in a dose-dependent manner. Besides, ANI increased the survival rate of tumor-bearing mice and suppressed the expression of NLRP3 in a dose-dependent manner. It is worth noting that NLRP3 overexpression reversed the inhibitory effect of ANI on HCC xenografts. In addition, TUNEL analysis showed that ANI-induced apoptosis of tumor cells, and NLRP3 overexpression reversed the inhibitory effect of ANI on HCC. Moreover, ANI further regulated the levels of IFN-γ, TNF-α, IL-4 and IL-27. Notably, low expression of NLRP3 enhanced the inhibitory effect of ANI on the development of HCC xenografts in mice.Discussion: These findings indicate that ANI suppressed the growth of HCC cells, induced apoptosis and regulated the levels of inflammatory factors by inhibiting NLRP3 inflammasome activation.Keywords: hepatocellular carcinoma, anisodamine, NOD-like receptor family pyrin domain containing 3, NLRP3, inflammatory factors, anticancer